2019
DOI: 10.3389/fonc.2019.00435
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations Profile of a Young Patient With Metastatic Urothelial Carcinoma Reveals Mutations in Genes Involved in Ion Channels

Abstract: Background: Urothelial carcinoma is the most common malignancy of the bladder and is primarily considered as a disease of the elderly. Studies that address bladder tumor occurrence in young age groups are rare. Case Presentation: A 19-year-old male presented with a gross total painless hematuria. A histology after biopsy revealed a high-grade transitional cell carcinoma with lymph node metastasis. The patient succumbed to the disease on day 72 of the treatment. Here, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In particular, Sharma et al. ( 45 ) also reported that the deleterious mutation of SPEN p.S1078* emerges as a putative potential therapeutic target in advanced-stage urothelial carcinoma. Additionally, we first analyzed the relationships between mutated distributions with a specific signature in the COSMIC dataset in two TMEscore groups.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Sharma et al. ( 45 ) also reported that the deleterious mutation of SPEN p.S1078* emerges as a putative potential therapeutic target in advanced-stage urothelial carcinoma. Additionally, we first analyzed the relationships between mutated distributions with a specific signature in the COSMIC dataset in two TMEscore groups.…”
Section: Discussionmentioning
confidence: 99%
“…CACNG1 (Voltage-dependent calcium channel gamma-1 subunit) encodes a muscle-specific isoform of the Ca 2+ channel gamma subunit. CACNG1 is increased in the lamina propria of the old rats, and the deleterious mutation is discovered in a young patient with metastatic urothelial carcinoma 33,34 . DUSP13 (Dual specificity protein phosphatase 13) encodes two atypical DUSPs, DUSP13B/TMDP and DUSP13A/MDSP, that are specifically expressed in testis and skeletal muscle respectively 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, negative results from clinical trials of targeted therapies suggest the need to identify novel biomarkers in regulating significant molecular mechanisms of ESCC progression ( Hirano and Kato, 2019 ). Alterations in ion channels, the membrane proteins that allow the influx and efflux of ions across membranes, have been reported in several tumors ( Sharma et al, 2019 ; Parthasarathi et al, 2022 ; Aydar et al, 2009 ; Chioni et al, 2010 ). Roles of ion channels in apoptosis and their potential in cell regulation and tumor progression were identified ( Comes et al, 2015 ; Fraser et al, 2014 ; Bustin et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%